Digital and mobile-enabled services help herder’s skills in addressing climate Change - Houessionon, Prosper; Hachim Said, Shakira; Worou, Nadine; Thiaw, Moussa; Chan, Derek; Wane, Abdrahmane; Whitbread, Anthony (International Livestock Research Institute, 2024)
The livestock sector in Senegal, a major contributor to greenhouse gas emissions, is highly vulnerable to climate change impacts such as droughts and extreme weather events. Climate information services (CIS) play a crucial role in enabling livestock farmers to adapt through climate-smart agricultural (CSA) practices. This study examines the impact of CIS on knowledge, attitudes, and the use of climate-smart livestock practices in Senegal. Using a Knowledge, Attitudes, and Practices (KAP) framework, data were collected from 800 livestock farmers in the Louga region through a randomized experiment. Results show that beneficiaries of CIS exhibited significant improvements in knowledge, attitudes, and the adoption of climate-smart livestock practices compared to non-beneficiaries. The findings underscore the effectiveness of CIS in facilitating behavioral change and highlight the need for broader dissemination to enhance adaptation across diverse farming communities. This study emphasizes CIS as a critical enabler for promoting sustainable livelihoods in the face of climate change.